A day in the life of a baby bear : the cub$1 (Bs first swim s - Barrett, Peter, 1935-; Barrett, Susan, 1938- (Mahwah, N.J. : WhistleStop, 1995)
A little bear$1 (Bs first swim almost becomes a disaster when a strong current sweeps her away from the shore.s
Keywords: Bears -- Juvenile fiction; Bears -- Fiction